PASAR TRADISIONAL DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI DESA KAYUAPAK KECAMATAN POLOKARTO KABUPATEN SUKOHARJO - Abdullah Zailani (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2016)
The aim of this study as follows (1) to determine the response of society based on the characteristics to the existence of traditional market Kayuapak Polokarto. (2) To determine the most dominant factor relation between the characteristics of the community and surrounding Polokarto on the existence of traditional market Kayuapak Polokarto. This research was conducted in Traditional Markets Kayuapak Polokarto. Population in this research is the entire community of users Kayuapak Polokarto Market. The samples were taken as many as 100 people using Cooper method. Problems statement in this study as follows: (1) How is the public response to the existence of traditional market Kayuapak Polokarto? (2) What factors most strongly linked between community characteristics and surrounding Polokarto on the existence of traditional market Kayuapak Polokarto? The Results of the study found that the presence of the market well received by the public Polokarto. There is a relationship between the role of the market with the characteristics of the user community. The most powerful relationship is the relationship between work and the role of traditional market Kayuapak Polokarto who helped create jobs for the community and surrounding Polokarto. The second sequence is the relationship between the income with the market's role in helping to improve the income regions, especially sub-district Polokarto, and the third is the relationship between education with the market's role as the community needs Polokarto. Â Â Keywords: traditional market, the characteristics of the community.